2014
DOI: 10.1097/nna.0000000000000059
|View full text |Cite
|
Sign up to set email alerts
|

Structural Empowerment of Clinical Nurse Managers

Abstract: In the current changing healthcare environment, it is important to gain more understanding of the role of CNMs who are crucial to quality care and patient and nurse satisfaction. This study provides important baseline information about perceptions of structural empowerment among CNMs. Interventions that can be initiated to enhance the CNM empowerment are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 11 publications
4
35
0
Order By: Relevance
“…These authors concurred in saying that a caring environment that recognizes NMs' leadership can have a significant impact on inter-professional collaboration, efficiency, management innovation, performance, and productivity. Our findings also support the work of Oliver, Gallo, Griffin, White, and Fitzpatrick, [48] who found that NMs' active participation in decision-making significantly increased job satisfaction and enhanced quality of care. Similar to Fyffe [49] and Paliadelis, [17] our findings demonstrated the importance of developing a political sense and understanding the strategic organizational power of nursing leadership.…”
Section: Discussionsupporting
confidence: 80%
“…These authors concurred in saying that a caring environment that recognizes NMs' leadership can have a significant impact on inter-professional collaboration, efficiency, management innovation, performance, and productivity. Our findings also support the work of Oliver, Gallo, Griffin, White, and Fitzpatrick, [48] who found that NMs' active participation in decision-making significantly increased job satisfaction and enhanced quality of care. Similar to Fyffe [49] and Paliadelis, [17] our findings demonstrated the importance of developing a political sense and understanding the strategic organizational power of nursing leadership.…”
Section: Discussionsupporting
confidence: 80%
“…The findings revealed moderate organizational trust for the subjects and in other studies, the nurses did not show a high rate of organizational trust in their managers (Laschinger & Finegan, 2005), and in their institutions (Altuntas & Baykal, 2010). Considering the results, it can be mentioned that factors such as lack of management support and not accessing to information reduce organizational trust , through daily briefing, newsletters, meeting with nurses, screen savers and electronic devices (Oliver et al, 2014) are important for achieving the organizational goals, as well as organizational trust and effectiveness.…”
Section: Discussionmentioning
confidence: 55%
“…These findings may suggest that nurses are not sufficiently supported by managers in order to create changes and innovations in their work settings. In Oliver's et al study conducted on the clinical nurse managers (CNMs), access to formal power showed the lowest mean (Oliver et al, ). Studies, found that emergency nurses in New Zealand (Connolly et al, ) and nurses in a teaching hospital in Turkey feel they have low levels of formal power (Dirik & Intepeler, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations